Product characteristic uncertainty in supply chains-cases from the food industry - Simangunsong, Eliot (Jurnal Manajemen Teknologi, 2012)
The food industry is a complex supply chain, where the path of a specific food product may vary and the supply chains within the food industry may have different structures from each other.Â  Another important characteristic of the food industry is the high frequency of new product introductions; this increases choice for consumers and initiates uncertainty related to product issues such as high product failure rates, short product life cycles and high inventory holding costs. Consequently, it is important to understand product characteristic as a source of supply chain uncertainty, how they can be managed and the resulting impact on performance. This paper presents a review of the available literature on supply chain uncertainty and related fields, highlights that although product characteristic has been identified as a source of uncertainty, insufficient empirical evidence has been presented. Multi-case study research, using semi-structured interviews, has been conducted across a group of inter-related companies in the food industry in Indonesia to investigate the role of product characteristic in creating uncertainty.Â  The result of analysis helps to refine the concept and provides a basis for detecting and managing product characteristic uncertainty, critical in the current competitive context. Keywords: Supply chain uncertainty; Food Industry; Uncertainty management